The comparison of meat yield, quality, and flavor between small-tailed Han sheep and two crossbred sheep and the verification of related candidate genes - Xiao, Cheng; Liu, Yu; Zhao, Wenjun; Liang, Yingjia; Cui, Chao; Yang, Shaoying; Fang, WenWen; Miao, Lisheng; Yuan, Zhiyu; Lin, Zihan; Zhai, Bo; Zhao, Zhongli; et al. (Frontiers in Nutrition, 2024)
Dorper or Australian white ram are generally crossbred with small-tailed Han (STH) ewe to improve the offspring's meat yield and quality in northeast China. However, the differences in that traits and flavor between the crossbred sheep and STH sheep remain unclear. Also, the candidate genes related to meat quality need to be verified in the three sheep. 18 2-month-old healthy rams were raised for 5 months including, 6 STH, Do x STH, and Au x STH offspring. The slaughter and meat quality traits, fatty acids and amino acids composition in the longissimus dorsi (MLD), and volatile compounds in the semitendinosus muscle were compared the differences among the sheep. The candidate genes related to intramuscular fat (IMF) content and fatty acids were verified. The results showed that the crossbred sheep had higher body, carcass, bone, net meat weight, and higher IMF content than the STH sheep (P＜0.05). The Do x STH offspring had higher a pH value (24 h), moisture content, cooking percentage, redder, and brighter meat color. The content of myristate, palmitic, and margaric acid in the crossbred sheep was higher than in the STH sheep (P ＜0.05). The Do x STH offspring had the highest saturated fatty acids content (P＜0.05). The Au x STH offspring had the highest protein content (P ＜ 0.05). Arachidonic acid and amino acids content (Asp, Ala, Ile, Leu, Lys, Thr, and essential amino acids) in the STH sheep were higher than in the crossbred sheep (P ＜0.05). Odor activity value (OAV) analysis showed that most of the aldehydes in the Au x STH offspring had higher values. The PDK4 gene expression was positively associated with IMF content and was negatively correlated with linoleic acid content in the Do x STH sheep (P ＜ 0.05). The TMEM273 gene expression was positively associated with linoleic and arachidonic acid content and was negatively correlated with oleic and palmitic acid content in the Do x STH sheep (P ＜ 0.05). The results showed the differences between the crossbred sheep and STH sheep and provided the candidates related to meat quality in sheep.